Impact of synoptic weather patterns and inter-decadal climate variability on air quality in the North China Plain during 1980–2013. (January 2016) - Zhang, Yang; Ding, Aijun; Mao, Huiting; Nie, Wei; Zhou, Derong; Liu, Lixia; Huang, Xin; Fu, Congbin
Abstract: Potential relationships between air quality, synoptic weather patterns, and the East Asian Monsoon (EAM) over the North China Plain (NCP) were examined during the time period of 1980–2013 using a weather typing technique and ground-based air pollution index (API) data from three cities: Beijing, Tianjin and Shijiazhuang. Using the Kirchhofer method, circulation patterns during the 34-yr study period were classified into 5 categories, which were further used to understand the quantitative relationship between weather and air quality in NCP. The highest API values were associated with a stagnant weather condition when wide-spread stable conditions controlled most part of NCP, while westerly and southerly wind flowed over the northern and eastern part of this region, resulting in both the regional transport and local build-up of air pollutants. Under the continuous control of this weather pattern, API values were found to increase at a rate of 8.5 per day on average. Based on the qualitative and quantitative analysis, a significant correlation was found between the strength of EAM and inter-annual variability of frequencies of the weather patterns. The strengthening of summer/winter monsoon could increase the frequency of occurrence of cyclone/anticyclone related weather patterns. Time series of climate-induced variability in API over the 34 years were reconstructed based on the quantitative relationship between API and predominant weather patterns during 2001–2010. Significant connections between EAM and reconstructed API were found on both the inter-annual and inter-decadal scales. In winter and summer, strengthening/weakening of EAM, which was generally associated with the change of the representative circulation patterns, could improve/worsen air quality in this region. Highlights: Synoptic weather patterns control air quality in the North China Plain. Intensity of East Asian Monsoon links to change in frequency of weather patterns. Variation in monsoon influence inter-annual and inter-decadal variations of API.